Teori Pengetahuan dan Kebenaran dalam Epistemologi - Sherly Aulia (Jurnal Filsafat Indonesia, 2022)
Epistemology as a branch of philosophy determines character, knowledge and even determines which truths are considered worthy of acceptance, and which ones should be rejected. Therefore, several questions are usually asked to examine issues in epistemology, namely what isknowledge, what are the sources and basis of knowledge? Is this knowledge a definite truth or isit just conjecture? To answer all the knowledge about epistemology, this article will examine moredeeply about the theory of knowledge and truth in epistemology. The method used in writing thisarticle is a literature study. After presenting several explanations from various literary sources so that it can be said that it is almost impossible to talk about "knowledge" without considering things about "truth". To know knowledge from right thinking processes, in the sense of being inaccordance with the search for knowledge, one must use right thinking in thinking. Truth that isnot true or false, or its truth based on conjecture cannot be considered as knowledge that isjudged to be true. Another condition for knowledge is truth, so we cannot claim to have knowledge of something that is not true